Barriers and facilitators for implementing the WHO's safety surgical checklist: A focus group study among nurses. Issue 12 (December 2018) - Georgiou, Εvanthia; Mashini, Maria; Panayiotou, Irene; Efstathiou, Georgios; Efstathiou, Christina Ioannidou; Charalambous, Melanie; Irakleous, Iraklis
The World Health's Organization's safety surgical checklist has been described as a means for increasing patient safety during surgical procedures. However, its full implementation has not yet been achieved worldwide. The aim of this study, via a focus group study among nurses, was to explore the factors that serve as barriers and facilitators for the list's implementation. Findings reveal that the use of the checklist can be compromised by many factors but also supported by others.